Pengaruh Perubahan Lahan Terhadap Suhu Iklim Mikro Urban Heat Island (UHI) di Kawasan Perkotaan Kabupaten Bulukumba - Kausar, Aksar; Ahmad, Despry Nur Annisa; Radhinal, Yan; Asman, Andi Idham; Sakti, Harry Hardian (Jurnal Peweka Tadulako, 2025)
Climate change and global warming have caused widespread environmental degradation. These impacts are directly experienced in Indonesia, particularly in the urban area of Bulukumba Regency, specifically in Ujung Bulu District. The increase in land use changes toward built-up areas has influenced the intensity of the Urban Heat Island (UHI) phenomenon. This study aims to analyze the effect of land use change on the Urban Heat Island (UHI) phenomenon in Bulukumba Regency during the periods of 2014, 2019, and 2024. A quantitative method was employed through satellite image interpretation to identify land use changes and analyze surface temperature using Landsat 8 Band 10 imagery data. The results indicate an increase in surface temperature in the urban area of Bulukumba Regency throughout the 2014–2024 period. The simple linear regression analysis shows a significant positive correlation between land use change and surface temperature increase, with a regression coefficient (r = 0.734) and a coefficient of determination (R² = 0.81), which falls into the high category. Furthermore, areas with high surface temperatures tend to follow the spatial pattern of densely built-up land use.